1983
DOI: 10.1128/aac.23.5.715
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of bovid herpesvirus 1 to antiviral drugs: in vitro versus in vivo efficacy of (E)-5-(2-Bromovinyl)-2'-deoxyuridine

Abstract: The relative efficacies of a variety of antiviral drugs against bovid herpesvirus 1 was investigated. (E)-5-(2-Bromovinyl)-2'-deoxyuridine and trifluorothymidine were found to be inhibitory at doses of 0.01 ,ug/ml in in vitro yield reduction and plaque reduction assays. In contrast, acylovir was inactive even at concentrations as high as 1,000 ,ug/ml. Other drugs, including phosphonoformic acid, 9-0-Darabinofuranosyladenine, 5-iodo-2-deoxyuridine, and 1-3-D-arabinofuranosylcytosine were active at concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

1984
1984
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…The authors demonstrated a greater activity of the alcoholic fractions in comparison to the aqueous extract, however these effect were demonstrated in therapeutic protocol. The difference in susceptibility to antiviral agents between HSV-1 and BoHV-1 was observed to acyclovir, due to mutations in the genes of the thymidine kinase (1). In this study we observed that extract was more effective in inhibiting HSV-1 infection.…”
Section: Discussionsupporting
confidence: 65%
“…The authors demonstrated a greater activity of the alcoholic fractions in comparison to the aqueous extract, however these effect were demonstrated in therapeutic protocol. The difference in susceptibility to antiviral agents between HSV-1 and BoHV-1 was observed to acyclovir, due to mutations in the genes of the thymidine kinase (1). In this study we observed that extract was more effective in inhibiting HSV-1 infection.…”
Section: Discussionsupporting
confidence: 65%
“…Certain kinasedeficient strains of herpesviruses, as well as many nonherpesviruses, are predictably resistant to the acyclic nucleoside analogues. 19 Because FHV-1 and some other herpesviruses are relatively resistant to acyclovir, some authors 12,16,[20][21][22] have suggested that these viruses lack the kinase necessary to initiate activation of acyclovir. The relatively high IC 50 for acyclovir in the study reported here confirms the relative resistance of FHV-1 to acyclovir.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro analyses of antiviral susceptibility have established the efficacy of brivudine against a number of clinically relevant viruses, most notably HSV-1 (14) and varicella-zoster (15). ence antiviral drugs against HSV-1 and 2.…”
Section: In Vitro Efficacymentioning
confidence: 99%